"The Red Dress or the Blue?": How Do Staff Perceive That They Support Decision Making for People With Dementia Living in Residential Aged Care Facilities?. (February 2016) - Fetherstonhaugh, Deirdre; Tarzia, Laura; Bauer, Michael; Nay, Rhonda; Beattie, Elizabeth
Respect for a person's right to make choices and participate in decision making is generally seen as central to quality of life and well-being. When a person moves into a residential aged care facility (RACF), however, decision making becomes more complicated, particularly if the person has a diagnosis of dementia. Little is known about how staff in RACFs perceive that they support decision making for people with dementia within their everyday practice, and this article seeks to address this knowledge gap. The article reports on the findings of a qualitative study conducted in the states of Victoria and Queensland, Australia with 80 direct care staff members. Findings revealed that the participants utilized a number of strategies in their intention to support decision making for people with dementia, and had an overall perception that "a little effort goes a long way."